AYAT AL-QUR - Alfianoor, Alfianoor (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2017)
The stimulating thing in the oral literature of the Banjar people is their mantras that custom parts or fragments of verses of the Qur'an. The usage of fragments of the Qur'anic verses in the mantra cannot be separated from their belief in the miracles of the Qur'an that are believed to provide the infiltrating force in the recited mantras, so as to, the purpose of chanting mantras in various shades is expected to achieved. According to the author, it is a form of interaction of an Islamic society against the Qur'an. the Banjar people are very religious, nonetheless they incorporate a very sacred and revered part of the Qur'anic verses and are upheld by Muslims in their mantras, as if this were a paradox. this is a very interesting thing to be studied.The research done in Hulu Sungai Tengah district has managed to get some important notes that the mantras that use the verses of the Qur'an turned out to exist in various kinds of spells such as in the spell of witchcraft, the spell of power, the mantra for things occult spells, spells to treat illness and praise.Keywords: Qur